Tax Holidays and Tax Noncompliance: An Empirical Study of Corporate Tax Audits in China's Developing Economy - Chan, K. Hung; Lan Mo, Phyllis Lai (The Accounting Review, 2000)
Many developing economies use tax holidays to attract foreign investment by providing a limited period of tax exemptions and reductions for qualified investors. This paper investigates the effect of tax holidays on foreign investors' tax noncompliance behavior in China's developing economy. We measure noncompliance in terms of tax audit adjustments the Chinese tax authorities require in response to avoidance and evasion. The results indicate that a company's tax-holiday position affects noncompliance. Companies are least compliant before entering a tax holiday, and most compliant while in a tax-exemption period. In addition, domestic market-oriented companies, service-oriented companies, and joint ventures are less compliant than export-oriented companies, manufacturing-oriented companies, and wholly foreign-owned enterprises, respectively. Our evidence is relevant to policymakers designing tax incentives to attract foreign investors. Our evidence on noncompliance should also help tax authorities and field auditors plan more effective and efficient tax audits. In addition, the results should provide researchers an interesting perspective to study the effect of tax-rate incentives on corporate tax noncompliance.